Influence of Project-Based Learning in the Teaching-Learning of History (Docentes 2.0 Journal, 2022)
Vygotsky's sociocultural theory of human learning describes learning as a social process and the origin of human intelligence in society and culture. This theory affirms that social interaction plays a fundamental role in the development of cognition and that learning occurs at two levels: through interaction with others. This research aimed to analyze the influence of Project-Based Learning (PBL) on teaching and learning history. It was based on the Research-Action method, a socio-critical paradigm, with a qualitative approach, with an exploratory-sequential design of a sequential type as emancipatory criticism. For a population of 30 students in the sixth grade of the Agricultural Technical Educational Institution of La Rinconada, Mompós, Bolívar. Likewise, information collection techniques and instruments were used in the methodology, such as direct non-participant observation, diagnostic and validation evaluation, and teacher survey. A pedagogical proposal was designed under the virtual modality due to the mandatory confinement by COVID-19. After the application of the projects, the strengthening of the teaching and learning process was evidenced because the teachers defined their role in the classroom and learned new innovative methodologies; the students were able to learn a method to develop school activities in an autonomous, active, participatory and meaningful way; and finally, improvement in academic performance was evidenced, strengthening skills, abilities, and competencies from the conceptual, procedural and attitudinal aspects in the subject of History.
Keywords: Project based learning; competences; history; teaching; learning